Manufacturing of soy protein concentrate for animal nutrition - Peisker M. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
Soy protein concentrate (SPC) is produced from defatted soy flakes. Soluble carbohydrates (oligosaccharides) are removed from the defatted flakes. Currently two methods are applied in the manufacturing of SPC: the extraction method or the enzymatic degradation of carbohydrates. The two methods lead to slightly different nutrient composition in the derived products. SPC has significantly higher nutritional value than soybean meal and is characterized by a low content of oligosaccharides (less than 3 per cent) and antigenic factors (less than 100-p.p.m. glycinin). SPC offers a cost efficient alternative to high quality proteins of animal origin such as skim milk powder or fishmeal in feeds for calves, piglets and pets. In aquaculture, SPC has a potential to replace up to 50 per cent fishmeal on a protein basis in diets for salmonids.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)